Influencia del gen WntA en los patrones alares de mariposas Mechanitis polymnia y Mechanitis lysimnia - Sánchez Prado, Mónica Paola (2025)
Butterfly wing patterns have evolved to serve functions such as aposematism, camouflage, mimicry, and sexual signaling. Multiple genes contribute to the development of these patterns, including WntA, which encodes a ligand involved in organizing color domains, particularly in the formation of black pattern elements. While the role of WntA has been well studied in model species like Heliconius, its function in non-model butterflies remains less understood. In this study, we used the CRISPR-Cas9 gene-editing system to characterize the function of WntA in Mechanitis lysimnia and M. polymnia. Somatic (mosaic) G₀ mutants were generated through embryo microinjections. Silencing WntA resulted in the loss of black pigmentation in both forewings and hindwings, accompanied by the expansion of yellow coloration in both species. This confirms WntA’s role as a regulator of the boundaries between color domains. In M. polymnia, yellow also expanded into orange regions. These findings provide functional evidence for the role of WntA in Ithomiini butterflies, extending our understanding beyond Heliconius and suggesting that conserved mechanisms may underlie wing pattern formation. This study also highlights the feasibility of applying CRISPR-Cas9 in non-model butterflies for evo-devo research.